ISOLASI DAN KARAKTERISASI SENYAWA STEROID PADA FRAKSI N-HEKSANA DARI DAUN KUKANG (Lepisanthes amoena (HASSK.) LEENH.) - M.Riza Agus Pramana; Chairul Saleh (JURNAL KIMIA MULAWARMAN, 2013)
Kukang (Lepisanthes amoena (Hassk) Leenh.) Leaves is one of the species that belonging to the Sapindaceae family. Traditionally used as drug ulcerate and skin care and also known it has potency of tironase inhibitor and antioxidant agent, but compound that contained in that plant was unknown. The purpose of this research was for isolating steroid compound of n-hexane fraction from Kukang (Lepisanthes amoena (Hassk) Leenh.) leaves and characterizing steroid compound with phytochemical screening, R f , melting point and IR spectrum. Extraction of 650 grams powder Kukang (Lepisanthes amoena (Hassk) Leenh.) leaves with methanol yielded 121,82 grams of crude methanol extract. The crude methanol extract was fractionated with n-hexane and obtained 2,32 grams of n-hexane fraction. Results of phytochemical screening showed that the n-hexane gave positive result for steroid compound. Separation of steroid compound in n-hexane fraction by column chromatography with silica gel 60 (70-230 mesh) which eluted using n-hexane : ethyl acetate (8 : 2) eluent based on Isocratic method and gave nine fractions. Phytochemical screening by Liebermann Burchard reagent showed F fraction contained steroid compound and have been crystalized needle. Purification by recrystallization of the F fraction gave the needle white crystal 10,2 mg with reterdation factor (R f ) n-hexane : CHCl 3 (1 : 1) = 0,40 ; n-heksana : CHCl 3 (3 : 7) = 0,50 CHCl 3 (100%) = 0,71 ; n-hexane : EtOAc (3 : 7) = 0,82 ; EtOAc (100%) = 0,86. Isolated compound has melting point 143-144°C, IR λmax (cm -1 ): 960,48; 1056,92; 1380,94; 1461,94; 1639,38; 2866,02;2935,46; 3433,06. Based on its physical and spectroscopic characterization, the isolated compound is supposed as sterol of steroid compound.